Análisis mutifrecuencia de la reflectividad del fondo marino para explorar la distribución superficial de sedimentos marinos al suroeste de Islas Hormigas de Afuera, costa afuera de Callao - Herbozo, Gery (2018)
The study of the sedimentary nature of the seafloor is a key aspect to infer the spatial distribution of demersal fisheries resources (e.g., hake (Merluccius gayi peruanus)), to locate adequate zones for aquaculture farms, to examine biogeochemical processes occurred in the water column and to estimate the abundance of benthic organisms lying at the seafloor (e.g., Thioploca). The aim of this study is to infer, using acoustic backscattering mutifrequency information from an EK60 scientific echosounder (200 kHz, 120 kHz, 70 kHz, 38 kHz, 18 kHz), the bulk composition of the first meter of marine sediments located to the southeast of Hormigas de Afuera Islands, offshore Callao. This hydroacoustic multifrequency system is routinely used for the assessment of fisheries resources for the Peruvian Sea Institute (IMARPE). In this study we used backscattering information (Sv mean) from the first meter below the sea bottom along a 7.5-km transect in the shelf (160 m water depth). This information represents the acoustic reflectivity of the investigated sediments. In addition, sediment sampling information from the seafloor was compiled to compare results from the reflectivity analyses. As result, we defined that there are six reflectivity patterns that would define certain types of surficial sediments. However, these patterns could not be compared to in-situ sediment samples because we found no historical sediment information along the studied transect. Reflectivity of the surficial sediment layer from three of the chosen patterns (p2, p4 and p5) may represent seafloor zones with hard substrata near the sea bottom (e.g., phosphorite crusts and/or small rocks of few cm thick) overlying fine- and coarsed-grained sediments (e.g., mud and coarse sands). Due to the acoustic permeability of one zone of this surficial layer, one of the observed patterns (p3) may represent fine-grained sediments associated to the mud lens. This type of sediment depocenters are composed by fine-grained, laminated sediments that are permeable to the acoustic energy (e.g., clays and/or a mix of fine-grained sediments). The two last patterns (p1 and p6), located at the northwest and southeast ends of the transect, may define zones with gas fronts in mud sediments. We conclude that it is not possible to classify sediment types based unambiguously on reflectivity information. However, the use of multifrequency reflectivity information does allow the characterization of sediment patterns. Such information needs necessarily to be calibrated with in-situ sediment samples in order to define the classification of marine surface sediment types at the seafloor where only hydroacoustic information is present.